Pengakuan Biaya Riset dan Pengembangan : Tinjauan terhadap SFAS No. 2 - Inon Listyorini (Universitas Muhammadiyah Yogyakarta, Indonesia, 2003)
SFAS No. 2 requires that research and development costs to be recognized as an expense in the period of issuance of such costs. Such treatment caused problems matching revenue with expenses can not be met, the concept of grouping resources as assets applied inconsistently and the trade off between the qualitative characteristics of relevance with reliability in the presentation of research and development costs. Capitalization of research and development costs can be done to overcome these problems, with the capitalization requirements made after the technical feasibility test.